Habitat Influence on the Metabolite Composition of Aglaomorpha propinqua and Its Biological Activity Studies - Chaudhary, Narendra Kumar; Rajbanshi, Pratibha; Guragain, Biswash; Budhathoki, Sujan; Bhattarai, Ajaya (Journal of Institute of Science and Technology, 2024)
In this study, we explore the phytochemical components of Aglaomorpha propinqua, a plant of the Polypodiaceae family, and their potential antibacterial effects on various pathogenic bacteria. Plant rhizomes from lithophytic and epiphytic habitats were selected for extraction using ethanol and water as solvents. The soxhlet method yielded 30.37% and 27.716% extracts in ethanol for epiphytic and lithophytic plants, respectively. Interestingly, unlike higher plants, this fern did not display many metabolites. Compared to the lithophytic plants grown at the same site and tested under similar conditions, higher zone of inhibition (ZOI) values were reported in epiphytic plants. The results were almost identical for the lithophytic plants (higher values of 9-10 mm and lower values of 6-9 mm). Evaluation of minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) provided additional support for antibacterial potency. Both epiphytic and lithophytic plants exhibited low MIC values, especially when interacting with K. pneumonia.